Cosmetics and their role in modulating skin microbiome health. A narrative review - Fatima, Munazza; Omer, Hiba; Nadeem, Nadia; Imtiaz, Saira (Journal of the Pakistan Medical Association, 2026)
The skin microbiome plays a vital role in immune regulation, barrier function, and protection against pathogens. Cosmetics, traditionally used for aesthetic purposes, also influence skin microbiomes. Depending on their formulation, they can support microbial balance through probiotics, prebiotics and postbiotics, or disrupt it, leading to dysbiosis and conditions such as eczema and acne. Advances in nanotechnology have further altered cosmetic efficacy and microbial interactions. The current narrative review was planned to highlight the dual role of cosmetics in modulating skin microbiome health, to emphasise the need for regulatory oversight, and to explore strategies for developing safe, microbiome-friendly skincare products. Key Words: Skin microbiome, Cosmetics, Nanotechnology, Probiotics, Prebiotics, Dysbiosis, Dermatological health.